2023
DOI: 10.1038/s41598-023-42596-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and subject-level drivers of interepidemic Rift Valley fever virus exposure in humans and livestock in Northern Kenya

Mathew Muturi,
Athman Mwatondo,
Ard M. Nijhof
et al.

Abstract: Nearly a century after the first reports of Rift Valley fever (RVF) were documented in Kenya, questions on the transmission dynamics of the disease remain. Specifically, data on viral maintenance in the quiescent years between epidemics is limited. We implemented a cross-sectional study in northern Kenya to determine the seroprevalence, risk factors, and ecological predictors of RVF in humans and livestock during an interepidemic period. Six hundred seventy-six human and 1,864 livestock samples were screened f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…Regarding brucellosis, goats had the highest prevalence than cattle. These findings align with previous research conducted in Uganda and Keny (Birungi et al, 2021;Kabami, 2023;Ndumu et al, 2021;Nyakarahuka et al, 2018aNyakarahuka et al, , 2023aNyakarahuka et al, , 2023bNyakarahuka et al, , 2023cNyamota et al, 2023;Tumusiime et al, 2023b).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding brucellosis, goats had the highest prevalence than cattle. These findings align with previous research conducted in Uganda and Keny (Birungi et al, 2021;Kabami, 2023;Ndumu et al, 2021;Nyakarahuka et al, 2018aNyakarahuka et al, , 2023aNyakarahuka et al, , 2023bNyakarahuka et al, , 2023cNyamota et al, 2023;Tumusiime et al, 2023b).…”
Section: Discussionsupporting
confidence: 92%
“…Multiple reports/samples taken from the same farm could have skewed distribution towards cattle, or it may be that farmers were more likely to report cattle due to their value. Previous studies in Uganda (Nyakarahuka et al, 2018(Nyakarahuka et al, , 2023a(Nyakarahuka et al, , 2023c and neighbouring countries like Kenya (Hassan et al, 2020;Muturi et al, 2023) have also found surprisingly low rates of reports of abortions in sheep. However, the small number of sheep included in the study, means we could not measure the (relative) risk of infection infection in this species.…”
Section: Such Call Centres Are Particularly Valuable For Animal Disea...mentioning
confidence: 88%
See 2 more Smart Citations
“…In East Africa, changes in climate (i.e., hotter and drier trends) and agricultural land-use change have increased the likelihood of infectious disease emergence and transmission, such as Ebola virus, Flaviviruses, Usutu viruses, Chikungunya and O’nyong-nyong viruses, Bunyaviruses, and Rift Valley Fever and Crimean-Congo haemorrhagic viruses (Duygu et al, 2018; Fanelli & Buonavoglia, 2021; Fenollar & Mediannikov, 2018; Muturi et al, 2023; Pandit et al, 2022). Further, a combination of climate, agricultural and economic changes are supporting the spread of emerging pathogens from East Africa into the Middle East and Europe (Ryan et al, 2019; Xiao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%